# OMTEX CLASSES

THE HOME OF SUCCESS

1. If the sum of π terms of an A.P. is equal to the sum of π terms, then show that the sum of its π + π
terms is zero.
Solution: Let π be the first term and π be the common difference of the given A.P.
We know that, ππ = π

2

2π + π β 1 π

But, ππ = ππ -------------------[given]
β΄ π π

2π + π β 1 π = 2π + π β 1 π
2
2

Cancelling

1
on both the side we get
2 π

2π + π β 1 π = π 2π + π β 1 π
β΄ π 2π + ππ β π = π 2π + ππ β π
β΄ 2ππ + π2 π β ππ = 2ππ + π 2 π β ππ
β΄ 2ππ β 2ππ + π2 π β π 2 π β ππ + ππ = 0
β΄ 2π π β π + π π2 β π 2 β π π β π = 0
β΄ 2π π β π + π π + π π β π β π π β π = 0
β΄ π β π 2π + π π + π β π = 0
β΄ 2π + π + π β 1 π =

0 π
βπ

β΄ 2π + π + π β 1 π = 0 ------------------------eq (1)
But, Sp+q =
β΄ ππ+π = π

+π
2

β΄ ππ+π = 0

p+q
2

[2π + π + π β 1 π]

0 -----------------------------[from equation number (1)]